A REVIEW ON THE DEVELOPMENT OF FAVIPRAVIR AGAINST SARS COV 2 INFECTION - B., VINOD (International Journal of Current Pharmaceutical Research, 2022)
Covid 19, the disease first identified in the Chine city of Wuhan in December 2019 had been declared as a pandemic by WHO. This pandemic caused by Sars Cov 2 has resulted in 165.5 million infections and 3.5 million deaths globally, as of now. Till now no drug isavailable to fight against this deadly disease. The strategy adopted by drug discovery groups is drug repurposing which has not met much success with chloroquine as well as remdesivir. A relatively new candidate in the fray is favipravir which was originally developed by Toyama chemical company against influenza strains. Few synthetic routes are developed for this compound and the safety concerns are relatively few. If favourable results from the ongoing clinicaltrials arise, that may provide the therapeutic community a lethalweapon against the virus.